Factor Service Quality, Harga dan Customer Satisfaction Terhadap Loyalitas Pelanggan (Studi Kasus Pada Balicosy Villa Legian Bali) - Ni Komang Ayu; I Ketut Selamet; Ida Ayu Putu Santi Purnamawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research is motivated by customer dissatisfaction with the quality of service provided by Balicosy Villa Legian, such as the condition of the room that is not clean enough. In addition, the differences in the results of previous studies are also the reason for the researcher to conduct this research in a different place. The main problem in this research is related to the influence of service quality, price, and customer satisfaction on customer loyalty at Balicosy Villa Legian in Badung Regency. This study aims to analyze the influence of service quality, price, and customer satisfaction on customer loyalty at Balicosy Villa Legian in Badung Regency, both simultaneously and partially with 119 research samples. The research method used is a quantitative method with data collection techniques through questionnaires and data analysis using multiple linear regression analysis. The results of the study indicate that service quality, price, and customer satisfaction simultaneously have a positive and significant effect on customer loyalty with a calculated F value of 15.153 and a significant value of 0.000. Partially, service quality has a significant positive effect on customer loyalty with a calculated t value of 3.420 and a significant value of 0.001. Price has a significant positive effect on customer loyalty, with a calculated t-value of 3.356 and a significance level of 0.001. Customer satisfaction has a significant positive effect on customer loyalty, with a calculated t-value of 4.170 and a significance level of 0.000.